PARTISIPASI LEMBAGA SWADAYA MASYARAKAT DALAM PEMBANGUNAN DAERAH DI KABUPATEN SIDRAP PROVINSI SULAWESI SELATAN - Abdul Rahman Abdul Rahman (Cakrawala Akuntansi & Manajemen, 2022)
The study about Non-Governmental Organization participation on development was set in Sidrap Religion, the province of South Sulawesi. It based on fact that religion development need more than governmental decision in all kind of policy. Non government organizations were increase in numbers on recent years. And they played role as determinant factor to control the design of development and to collect people participation accros the area. This research is focused at the effort to answer the problem of how nongovernmental organization took its participation on region development, and what is the government efforts to increase level of participation along those organization. Using qualitative approach, the researcher as research instrument collected, processed, analyzed, interpreted and verified all of information and data from participatory observation on the setting which discribe comunication and relationship between government and non-governmental organization. Data and information obtained through participation observation were, then, enriched and completed by unstructured interview to the good informants who meet the reach cases prerequisites, so its validity and reliability could be counted on. Afterwards, data and information were clarified, described, and explained using triangulation method with any social sciences theories, government sciences and the researcher's knowledge in order to formulate the answer of research questions. The research findings pointed out that participation of non-governmental organization is constitude as well as what Davis constructed on his theory. Davis believes that participation are form from emotional involvement, situation of groups, contribution to the aim and sharing responsibility. This research found all element on non- governmental participation, but its still limited. Furthermore, participation culture is weak among non-govenmental organization. Seeing this problem it is recommend that government its self that could take an initiative to empowering all non- governmental organization. Through this, the level of participation could be increased, hipotetically.